Pengembangan Buku Ajar Botani Tumbuhan Rendah Bermodel 4D (Define, Design, Defelop, Disseminate) dan Pengaruhnya terhadap Kemampuan Berfikir Kritis, Kesadaran Metakognitif dan Hasil Belajar Mahasiswa IAIN Ambon - Mulyawati, Nina Yuliana; Masi, Yusman; Rijal, Muhammad (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
This research aims to find out the use of Low Plant Botany textbooks developed with valid 4D models and their influence on critical thinking ability, metacognitive awareness and learning outcomes as well as the interaction of low plant botany textbooks developed with 4D models with academic ability to critical thinking ability, metacognitive awareness and student learning outcomes of IAIN Ambon Department of Biological Education so as to provide theoretical and practical benefits to lecturers and students. This research was conducted in the odd semester of the 2016/2017 academic year, on July 25-November 1, 2016. The research sample was taken by purposive sampling using the Experimental Pretest-Posttest Nonequivalent Control Group Design. The data that has been collected was analyzed using analysis of covariance (anacova). The results showed that (1) the Low Plant Botany textbook developed with the 4D model could be used validly (2) there was an effect of the Low Plant Botany textbook developed with the 4D model on critical thinking skills (3) there was the influence of the Low Plant Botany Textbook. which was developed with the 4D model on metacognitive awareness (4) there was an influence of the Low Plant Botany Textbook developed with the 4D model on cognitive and affective learning outcomes (5) there was an interaction effect of the Low Plant Botany Textbook developed with the 4D model with academic ability with the ability critical thinking, cognitive learning outcomes and psychomotor learning outcomes. Based on the results of the study, it can be concluded that the Low Plant Botany Textbook developed with the 4D model can be used validly and has an effect on critical thinking skills, metacognitive awareness, cognitive and affective learning outcomes and there is an interaction effect with academic abilities on critical thinking skills, cognitive learning outcomes and psychomotor. It is recommended to collaborate with biology textbooks with appropriate learning models and strategies. Keywords: Development, Textbooks, Define, Design, Develop, Disseminate, Critical Thinking, Metacognitive Awareness, Learning Outcomes